Iowa RBA, December 11, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Iowa RBA update for December 11, 1995. Highlights of the update include sightings of a Black-billed Magpie, Common Redpoll, Prairie Falcon and a pair of Evening Grosbeaks. Also included are handwritten notes for the next week's update with sightings of a Golden-crowned Kinglet and a Yellow-rumped Warbler. Epson - sheet feed/flatbed